Lifestyle interventions for non-alcoholic fatty liver disease - Ahmed, Idris Adewale; Mikail, Maryam Abimbola; Mustafa, Mohd Rais; Ibrahim, Muhammad; Othman, Rozana (Elsevier B.V., 2019)
Non-alcoholic fatty liver disease (NAFLD) is a multi-factorial disease and the most common of chronicliver diseases worldwide. The four clinical-pathological entities which are usually followed by NAFLDcourse include non-alcoholic steatosis, non-alcoholic steatohepatitis, advanced fibrosis/cirrhosis, andhepatocellular carcinoma. The cornerstones of NAFLD management and treatment, however, are healthylifestyles such as dietary modifications, regular physical activity, and gradual weight loss. At present, nodrugs or pharmacological agents have been approved for long-term treatment of NAFLD. Therefore, life-style modification is considered the main clinical recommendation and an initial step for the manage-ment of NAFLD